2021
DOI: 10.5935/0103-507x.20210051
|View full text |Cite
|
Sign up to set email alerts
|

Early Rehabilitation Index: translation and crosscultural adaptation to Brazilian Portuguese; and Early Rehabilitation Barthel Index: validation for use in the intensive care unit

Abstract: Objetivo Traduzir, adaptar transculturalmente para o português do Brasil o instrumento Early Rehabilitation Index e validar para uso na unidade de terapia intensiva o instrumento Early Rehabilitation Barthel Index , para avaliação do estado funcional. Métodos Foram executadas as seguintes etapas: preparação, tradução, reconciliação, tradução reversa, revisão, harmonização, pré-teste e avaliação psicométrica. Após ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Similarly, the 15-item BI also demonstrated a narrow assessment precise width (−1 < θ < 1) (Zhao et al, 2022 ). Furthermore, reports of ceiling effects (>15% of the sample attaining the maximum score) and floor effects (>15% of the sample scoring the minimum) have been reported across different populations, such as patients with stroke (Balu, 2009 ), patients in the intensive care unit (Reis et al, 2021 ), and older hospitalized patients with cognitive spectrum disorders (Braun et al, 2021 ). These observations suggest an inherent limitation in the BI's measurement due to its focus on a limited range of ADLs and the absence of assessment beyond basic ADLs (Bouwstra et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the 15-item BI also demonstrated a narrow assessment precise width (−1 < θ < 1) (Zhao et al, 2022 ). Furthermore, reports of ceiling effects (>15% of the sample attaining the maximum score) and floor effects (>15% of the sample scoring the minimum) have been reported across different populations, such as patients with stroke (Balu, 2009 ), patients in the intensive care unit (Reis et al, 2021 ), and older hospitalized patients with cognitive spectrum disorders (Braun et al, 2021 ). These observations suggest an inherent limitation in the BI's measurement due to its focus on a limited range of ADLs and the absence of assessment beyond basic ADLs (Bouwstra et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect muscle strength was measured using the Medical Research Council Sum-Score (MRC-SS) 20 . Participants were considered eligible to participate in the study if they responded at least three of the ve commands proposed by De Jonghe 21 : "open/close your eyes"; "look at me"; "open your mouth and put out your tongue"; "nod your head"; and "raise your eyebrows when I have counted up to ve".…”
Section: Assessment Protocolmentioning
confidence: 99%
“…The MRC-SS is a simple tool for assessing global muscle strength in intensive care patients and has good inter-rater reliability 22 . The tool has been translated into Portuguese and adapted for use in Brazil 20 .…”
Section: Assessment Protocolmentioning
confidence: 99%
“…Although ERBI has been administered in several studies in persons with sABI, 13 , 14 its psychometric properties were assessed in detail by few studies. 7 , 15 , 16 Particularly, Rollnik et al 15 demonstrated high correlations between nurses’ and physicians’ assessments (r=0.849) and moderate correlations with BI (r=0.438 and r=0.430 if administrated by nurses of physicians, respectively) in 273 neurological rehabilitation patients. 15 Furthermore, Reis et al 16 showed that a Brazilian Portuguese version of the ERBI had a moderate to excellent inter-rater reliability (kappa ranging from 0.54 to 1.00) and that its total score correlated significantly with several other functional indicators in 122 patients admitted to the general intensive care unit.…”
mentioning
confidence: 98%
“… 15 Furthermore, Reis et al 16 showed that a Brazilian Portuguese version of the ERBI had a moderate to excellent inter-rater reliability (kappa ranging from 0.54 to 1.00) and that its total score correlated significantly with several other functional indicators in 122 patients admitted to the general intensive care unit. 16 Finally, Rollnik et al. 15 , 17 demonstrated the predictive validity of low ERBI total scores in terms of significantly longer length of stay 15 , 17 and significant morbidities.…”
mentioning
confidence: 99%